Correlation Between CEA Serum Level on NSCLC Patients with EGFR Mutation from Tissue and Plasma Sample - Frenky Hardiyanto Hendro Sampurno; Suryanti Dwi Pratiwi; Ngakan Putu Parsama Putra (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Patients with NSCLC can have EGFR mutation and increased level of CEA. EGFR mutation test on NSCLC has very important role for EGFR tyrosine kinase inhibitor (TKI) therapy.CEA is also expected to predict treatment efficiency of EGFR-TKI therapy. Tumor tissue biopsy is an invasive method and has come constraints, despite the golden standard testing. Circulating tumor DNA (ctDNA) is a new and less invasive for detecting EGFR mutation using plasma sample. In this study, we investigated the relationship between serum CEA and EGFR mutations in tissue and plasma in NSCLC patient.Methods: This cross-sectional observational research was conducted in Dr. Saiful Anwar General Hospital Malang from August 2018 until July 2019, 76 NSCLC patients who had undergone test of EGFR mutation from tissue, ctDNA, and serum CEA level. Extracted DNA from plasma and tissue samples from citology or biopsy was checked for the EGFR mutation. The serum CEA levels were analyzed using electrochemical luminescence.Results: EGFR mutation from tissue samples positive detected on 34 subjects and ctDNA detected 19 subjects. Serum level of CEA >5 ng/ml was significantly associated with EGFR mutation from tissue sample (p=0.037) with an odds ratio of 2.778 (95% CI: 1.050-7.348), the area under curve for CEA was 68,8% and cut-off CEA 9.14 ng/ml. Serum level of CEA >5 ng/ml wasalso significantly associated with ctDNA (p=0.015) with an odds ratio of 4.8 (95% CI: 1.259-18.299), the area under curve for CEA was 78,1% and cut-off CEA 14.8 ng/ml.Conclusion: Serum CEA level has poor correlation with mutation of EGFR from tissue and moderate correlation with mutation of EGFR from ctDNA in NSCLC patients. Patients with increased level of CEA >5 ng/ml are 2.778 times more at risk to had EGFR mutation and 4.8 times more at risk to had ctDNA positive mutation.